Impact of Integrating Social and Health Home Care Services in Catalonia: A Retrospective Cohort-Based Two-Year Study - Vela, Emili; Contel, Joan Carles; Vila, Anna; Santaeugènia, Sebastià J.; Suñol, Rosa; Amblàs-Novellas, Jordi; Barbeta, Conxita; Plaza, Aina; Hilarión, Pilar (International journal of integrated care, 2025)
Introduction: This study aimed to evaluate the impact of integrating social and health home care services (HCSs) on institutionalization, survival, and utilization of health and social care services and associated expenditures. Methods: Retrospective study including all individuals who initiated social HCSs for dependent people in Catalonia during 2018–2019 with a paired case-control, pre/post design (differences-in-differences), using integrated data from the Autonomy and Dependency Care System database and the Catalan Health Surveillance System. Individuals were categorized based on their perceived level of integration in the residing areas (high level: Case Group, and low level: Control Group). Results: We included 4381 cases and 13143 matched controls. HCS integration decreased the risk of institutionalization in a nursing home by 19.5% and the length of stays in any center by 7.7%. Integration increased day centers’ use by 23.7% and primary care service utilization by 3.0%, and also reduced associated social expenditures after HCS initiation by 19.1% and overall social and health expenditures by 2.6%. Conclusion: Integration of social and health HCSs resulted in a shift from institutionalization services to primary care services and day care centers, prolonging recipients’ lives in their homes.